Long‐term outcomes of patients with Crohn's disease who received infliximab or adalimumab as the first‐line biologics. Issue 8 (27th February 2019) - Inokuchi, Toshihiro; Takahashi, Sakuma; Hiraoka, Sakiko; Toyokawa, Tatsuya; Takagi, Shinjiro; Takemoto, Koji; Miyaike, Jiro; Fujimoto, Tsuyoshi; Higashi, Reiji; Morito, Yuki; Nawa, Toru; Suzuki, Seiyuu; et al.
Abstract: Background and Aim: Although previous studies compared the efficacy of infliximab (IFX) versus adalimumab (ADA) as the first‐line biologics for Crohn's disease (CD), the difference in long‐term prognosis based on which biologic was used first has scarcely been reported. In particular, the clinical courses after loss of response (LOR) of the first‐line biologics are largely unknown. Methods: A multicenter, retrospective study was performed. Disease courses of biologic‐naïve CD patients who were started on IFX or ADA treatment were evaluated, even after LOR of the initial biologics. Results: In total, 263 CD patients were eligible for analysis, 183 were treated with IFX first, and 80 were treated with ADA first. The median observation period was 64.2 months. The cumulative steroid‐free remission rates and surgery‐free rates did not differ significantly between the patients treated with IFX first and those treated with ADA first (log‐rank test P  = 0.42 and P  = 0.74, respectively). In addition, no significant difference was observed in the rate of occurrence of events associated with ineffectiveness (modification of anti‐tumor necrosis factor treatment including intensification, switch, discontinuation, or surgery) between the patient groups (log‐rank test P  = 0.62). The patients treated with IFX first were likely to discontinue the agent due to adverse events, whereas those treated with ADA first were likely to discontinue due to treatment failure or LOR. Conclusions: No significant difference was observed in the long‐term prognosis between biologic‐naïve patients with CD who were started treatment with IFX first and ADA first.